GC-MS ANALISIS TERHADAP KUALITAS MINYAK KAYU PUTIH ASAL PELITA JAYA KABUPATEN SERAM BAGIAN BARAT PROVINSI MALUKU - Jimmy Johanso Fransz; Rohny Setiawan Maail; Jimmy Titarsole (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2019)
This study was conducted to determine the Melaleuca cajuput Powell oil from Pelita Jaya Village on West of Seram Regency for more detail by using Gas Chromatography-Mass Spectrometry (GC-MS). Testing characteristics of phisycal properties was used SNI 06-3954-2001 which covers the specific of weight at 15Â°, odor, optical rotation, solubility in alcohol, fatty oil while the quality testing through chemical compounds content composition were used GC-MS. The results showed that the specific of weight requires the standard in value of 0.919, typical-green light color, there is no mixing with other oils and no fat oil with an optic rotation value of 3, 80o. GC-MS analysis proved that the quality of Melaleuca cajuput oil from Pelita Jaya village is very good with cineole content is classified as first level (P) and main (U) with a value of 60.17% and is required standard range of 24-64%.